2015
DOI: 10.1177/1933719114549850
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Pharmacology and Pharmacokinetics of Ulipristal Acetate for the Treatment of Uterine Fibroids

Abstract: Uterine fibroids are benign hormone-sensitive tumors of uterine smooth muscle cells leading to heavy menstrual bleeding and pelvic pain. Ulipristal acetate (UPA) is an emerging medical treatment of fibroids with the potential to be used for long-term treatment. In this context, the present article summarizes UPA's main clinical pharmacology and pharmacokinetic (PK) properties. Ulipristal acetate has good oral bioavailability and a half-life allowing one single oral administration per day for the management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…P4 concentration was 13.05 ± 1.14 ng/ml. UPA concentration was 63.49 ± 10.46 ng/ml which was the same range observed in clinical use [64]. Hormone levels were undetectable in control mice (E2 < 0.8 pg/ml; P4 < 0.4 ng/ml; UPA < 0.5 ng/ml).…”
Section: Methodssupporting
confidence: 69%
“…P4 concentration was 13.05 ± 1.14 ng/ml. UPA concentration was 63.49 ± 10.46 ng/ml which was the same range observed in clinical use [64]. Hormone levels were undetectable in control mice (E2 < 0.8 pg/ml; P4 < 0.4 ng/ml; UPA < 0.5 ng/ml).…”
Section: Methodssupporting
confidence: 69%
“…C max increased in linear dose dependent manner up to 100 mg [8]. UPA is extensively metabolized in the liver by cytochrome p450 (CYP) 3A4 via N-demethylation of its dimethyl-amino phenyl group to form aniline-like metabolites and 73% of administrated dose is eliminated in feces [9]. Elevated levels of liver enzymes in few clinical studies, suggestive of undesired liver effects, have been observed for UPA [10].…”
Section: Ulipristal Acetatementioning
confidence: 99%
“…UPA is metabolised via cytochrome P450 3A4, and thus a reduction of efficacy may occur when drugs known to induce cytochrome induction, are used. These include rifampicin, dabrafenib, enzalutamide, certain anti‐epileptic drugs such as primidone, phenytoin or carbamazepine and St John's wort . Whether women who breast feed should use UPA is controversial as it may be excreted in their milk …”
Section: History and Mechanisms Of Actionmentioning
confidence: 99%